BIRDS OF THE WETLANDS OF THE CALLAO REGION: UPDATE AND CONSERVATION STATUS - Podestá, Jorge (2021)
The wetlands of Callao have a variety of aquatic flora and fauna. These oases (Ventanilla Wetlands Regional Conservation Area (ACRHV), El Mirador Municipal Ecological Park and the Poza de la Arenilla-HCPA Coastal Wetland) are a great attraction for tourism and bird watching. However, there is only one wetland with protection status: Ventanilla Wetlands Regional Conservation Area (ACRHV). Although the other two wetlands are not protected, there are initiatives for their conservation. The importance of this article lies in identifying the bird species that these wetlands harbor, as well as having accurate information on the resident and migratory birdlife. The Jaccard similarity index was calculated to 1) determine the similarity in species composition between the three wetlands: ACRHV, El Mirador and HCPA, and 2) determine the similarity between the same seasonality categories for ACRHV + El Mirador and HCPA. The families with the highest richness were Scolopacidae (22) and Laridae (14). Regarding seasonality, the main difference observed between the wetlands located in the Ventanilla district (ACRHV and El Mirador) and La Punta (HCPA) is in resident species (Re), with 55 species for Ventanilla and 24 species for La Punta. In relation to similarity according to seasonality, the greatest Jaccard similarity was obtained by boreal migratory species, with almost 59% species being shared between the Ventanilla district and La Punta. The results of this study show the close relationship that exists between the three wetlands of Callao, which are shared habitats for many species of birds. These results would promote actions for the management of these ecosystems at the regional level, such as the creation of an important biological corridor in the central zone of Lima and Callao.